2008
DOI: 10.1021/jo8017473
|View full text |Cite
|
Sign up to set email alerts
|

Six-Membered Ring Phosphates and Phosphonates As Model Compounds for Cyclic Phosphate Prodrugs: Is the Anomeric Effect Involved in the Selective and Spontaneous Cleavage of Cyclic Phosphate Prodrugs?

Abstract: In recent years, several six-membered ring phosph(on)ates and phosphonamides have been reported as potent prodrugs against liver diseases such as hepatitis B and C and also as antitumor agents. Apparently, the success for their biological activity depends on the selective cleavage of the C4-O3 bond within the respective P-heterocyclic ring. Empirical observations have suggested that the group attached to the C4 position (aryl or pyridyl group) is responsible for the selective cleavage. In this regard, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Conformers C2 and B2 (of which B2 has been proposed for related cyclic phosphates) 20,21 were not considered in the study: first, because equilibrium C1 h B1 was supported having trapped both conformers in the solid state within the same crystal lattice (for R = Ph, equatorially oriented in C1), 18 second, because equilibrium C1 h T could be established based on NMR data, and third because conformation T was corroborated by an X-ray crystallographic study for R = p-Cl-Ph (Scheme 3). 15,18 The four above-mentioned conformations were established in solution and corroborated by X-ray crystallographic studies for phosphates with both R P and S P configuration, and having an equatorial oriented R group. The only conformation that has not been corroborated by X-ray diffraction analysis is that having an axially oriented aryl group at the C4 position.…”
Section: Jocarticlementioning
confidence: 79%
See 1 more Smart Citation
“…Conformers C2 and B2 (of which B2 has been proposed for related cyclic phosphates) 20,21 were not considered in the study: first, because equilibrium C1 h B1 was supported having trapped both conformers in the solid state within the same crystal lattice (for R = Ph, equatorially oriented in C1), 18 second, because equilibrium C1 h T could be established based on NMR data, and third because conformation T was corroborated by an X-ray crystallographic study for R = p-Cl-Ph (Scheme 3). 15,18 The four above-mentioned conformations were established in solution and corroborated by X-ray crystallographic studies for phosphates with both R P and S P configuration, and having an equatorial oriented R group. The only conformation that has not been corroborated by X-ray diffraction analysis is that having an axially oriented aryl group at the C4 position.…”
Section: Jocarticlementioning
confidence: 79%
“…With this information in mind, it was recently proposed, based on simple model phosphates, that the anomeric effect is involved in the spontaneous cleavage of cyclic phosph(on)ate prodrugs. 15 The spontaneous conversion of unstable cyclic phosphates (E) to their most stable cyclic phosphates (F) demonstrates that isomerization is favored by natural hyperconjugation between the nO nonbonding and σ*-P-X antibonding orbital (anomeric effect), which generates the double-bonded non-bonding resonance structure (G), thus weakening the O3-C4 bond and favoring the selective and spontaneous cleavage of the phosphate ring (G h H); finally, after a rapid collapse of the phosphate group, the more stable cyclic phosphate F is formed (Scheme 2). Additionally, it was also postulated that the steric hindrance caused by the 1,3-syn diaxial interaction between aryl and phenoxy groups influences the O3-C4 bond cleavage, even though the chair conformation has been found to be less favorable.…”
Section: Jocarticlementioning
confidence: 99%
“…The synthesis of 5-aryl-5-ulose xylo derivatives 1a–d was achieved in three steps from xylo furanose tosylate derivative 5 . First, a two-step one-purification protocol involving a tandem nonaqueous hydrolysis of the 5,6- O -isopropylidene moiety of 5 to the transient aldehyde (not shown), which was transformed into a diastereomeric mixture of alcohols 6a–d by the addition of the corresponding Grignard . Oxidation of 6a–d with PCC afforded ketones 7a–d , which were transformed into the target compounds after being treated with K 2 CO 3 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one from about 20 structures of 3 0 :5 0 -cyclic nucleotides and their derivatives deposited with the CSD reveals a significant deformation of the chair conformation (Nelson et al, 1987). A non-chair conformation was observed in the structure of a conformationally restricted dinucleotide analogue (Le Clé zio et al, 2005) and xylofuranose cyclic phosphate derivatives (Sartillo-Piscil et al, 2003;Cruz-Gregorio et al, 2009). Steric, stereoelectronic and other factors influencing the conformation of six-membered phosphates have been extensively studied over the past decade (Cruz-Gregorio et al, 2005, 2009Quintero et al, 2010) and the importance of the skew conformation in cellular media was shown (Nelson et al, 1987;Le Clé zio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%